Navigasi Psikologis dalam Pendidikan: Mengoptimalkan Efektivitas Belajar Berbasis Tahap Perkembangan dan Batasan Usia - Rizki Ni’matul Khasanah; Abdul Khobir; Alfiyatun Nur Fadhilah; Najwa Nafi’ah Zahra; M. Adham Adil Santoso (Lembag, 2026)
This study aims to provide the benefits of a psychological approach in education through a learning adjustment strategy based on the developmental stage and age limits of students. The study used a library method with a qualitative descriptive-analytical approach through a review of educational psychology literature, cognitive development theory, national education regulations, and various relevant scientific journals. The results of the study indicate that learning effectiveness is greatly influenced by the alignment between material, teaching methods, and students' psychological readiness. Piaget's cognitive development theory indicates that elementary school-aged children are at the concrete operational stage, thus requiring contextual learning, the use of real-life media, and active interaction in the learning process. This study also found that age limits in the education system have an important function as a means of synchronizing students' biological, emotional, social, and intellectual readiness with learning targets. Through the